Cardiovascular Responses Associated with Daily Walking in Subacute Stroke - Sanjay K. Prajapati; Avril Mansfield; William H. Gage; Dina Brooks; William E. McIlroy (Stroke Research and Treatment)
Despite the importance of regaining independent ambulation after stroke, the amount of daily walking completed during in-patient rehabilitation is low. The purpose of this study is to determine if (1) walking-related heart rate responses reached the minimum intensity necessary for therapeutic aerobic exercise (40%–60% heart rate reserve) or (2) heart rate responses during bouts of walking revealed excessive workload that may limit walking (>80% heart rate reserve). Eight individuals with subacute stroke attending in-patient rehabilitation were recruited. Participants wore heart rate monitors and accelerometers during a typical rehabilitation day. Walking-related changes in heart rate and walking bout duration were determined. Patients did not meet the minimum cumulative requirements of walking intensity (>40% heart rate reserve) and duration (>10 minutes continuously) necessary for cardiorespiratory benefit. Only one patient exceeded 80% heart rate reserve. The absence of significant increases in heart rate associated with walking reveals that patients chose to walk at speeds well below a level that has meaningful cardiorespiratory health benefits. Additionally, cardiorespiratory workload is unlikely to limit participation in walking. Measurement of heart rate and walking during in-patient rehabilitation may be a useful approach to encourage patients to increase the overall physical activity and to help facilitate recovery.